Youth, enterprise and precarity: or, what is, and what is wrong with, the 'gig economy'?. (December 2019) - MacDonald, Robert; Giazitzoglu, Andreas
By taking an historical perspective, and by drawing on our own empirical work from the UK in the 1980s and more recently, we argue three main things. First, we need to understand the particular conditions of 'the gig economy' as a concentrated form of a more general de-standardisation of employment that has brought multiple forms of insecure work. Second, although there is clamour and excitement about 'the gig economy' in fact it shares strong parallels with earlier forms of insecure enterprise. Third, while not uniform nor as yet fully empirically demonstrated, young adults' encounters with the 'gig economy' and other aspects of the contemporary labour market (such as the 'low-pay, no-pay' cycle, self-employment, 'zero-hours contracts') appear to be typified by a lack of choice and control, and experiences of disempowerment, low pay, degraded work conditions, alienation, anxiety and insecurity. This stands at odds with more celebratory proclamations about 'the gig economy'.